BRINE SHRIMP CYTOTOXIC ACTIVITY OF 50% AQUEOUS ETHANOLIC LEAF EXTRACT OF CALOTROPIS PROCERA R. BR - SK, SURAJ; CHATTERJEE, PADMA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of this work entails a preliminary screening of 50% aqueous ethanolic leaf extract of Calotropis procera for locating antitumor activity. Methods: 50% aqueous ethanolic extract, obtained from dried powdered plant material of C. procera was partitioned sequentially in petroleum ether, benzene, and chloroform. Each fraction thus obtained was concentrated in a vacuum evaporator. The residual mass was collected separately and dissolved in propylene glycol. The three samples were subjected to brine shrimp cytotoxic assay to locate if there may be any positive response of antitumor activity. Result: It was found that the sample obtained from chloroform extract responded positively in brine shrimp test and showed lethal concentration (LC 50 at which 50% individual dies) at the concentration of 5 mg/ml. Benzene extract showed LC at the concentration of 15 mg/ml and petroleum ether showed LC 50 at the concentration of 20 mg/ml. Conclusion: Proves the presence of antitumor phytochemicals in C. procera. Keywords: Antitumor compounds, Brine shrimp, Calotropis procera, Cytotoxic activity.